Reputation and Firm Performance: A Research Agenda - Ayaz, İlke Sezin and Sigalı, Seçil (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Various researchers have investigated the reputation and firm performance relationship with the perspectives of different disciplines. This study is a semi-systematic literature review that examines articles in top-ranked journals to analyze how the reputation and firm performance relationship has evolved in terms of theoretical backgrounds, variables, methodologies and the scope of the reputation-performance relationship. Classifications of the reputation and firm performance relationship articles are highlighted in four broad areas: financial performance, sustainability performance, marketing performance and organizational performance. The results of this study showed that the number of the published articles has increased gradually through the analysis period, and majority of the articles investigated the firm reputation and financial performance relationship. Due to the results a research agenda is developed for future research.